Intra-articular Sodium Hyaluronate in Comparison with Corticosteroids for the Management of Osteoarthritis of Knee Joint - SAADIA TARIQ, ILLYAS IDREES, ARIQ SAEED, NASRULLAH KHAN, TARIQ MASOOD (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVE: To assess and compare the role of intra articular hyalurnic acid [HA] for the management of osteoarthritis of knee joint in comparison with the intra articular injection of corticosteroids. DESIGN: It is a comparative and analytical study. PLACE & DURATION OF STUDY: This study was carried out in surgical unit III Fauji Foundation Hospital , Rawalpindi and at Choa Khalisa a town 40 kilometres from Rawalpindi in the period from January 2008 – March 2009 RESULTS: The highest prevalence of Hyaluronic Acid [HA] use was in the 70–79 year age group in both sexes. Women received intra-articular HA treatment more frequently than men in all age groups, especially in the 60–69 and 70–79 year groups (1.6% vs. 0.5%, 2.2% vs. 1.0%, respectively). A total of 100 patients were included in this study,79 79% patients were females and 21 [21%] were males. who presented in the outdoor patient department of fauji foundation hospital and Choa Khalisa with complaints of a pain and sittness of the knee joints.. CONCLUSION: we conclude that intra-articular Hyaluronic Acid might be a good alternative for patients for whom conventional treatment fails especially in younger age groups60-69. Whereas the corticosteroids are effective in acute cases where they give relief especially if combined with lidocaine or bupivacain but it has no long lasting effects. Intraarticular Hyaluronic acid should be reserved for patients in whom conventional treatment fails and who are comparatively young. Further research is needed to examine the age-gender differences in use of intra-articular Hyaluronic Acid.